2020
DOI: 10.21203/rs.3.rs-15629/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of a free healthy school meal on fruit, vegetables and unhealthy snacks intake in Norwegian 10- to 12-year-old children

Abstract: Background: Norwegian children have a lower intake of fruit, vegetables, and a higher intake of unhealthy snacks compared to dietary guidelines. Such dietary inadequacies may be detrimental for their current and future health. Schools are favorable settings to establish healthy eating practices. Still, no school meal arrangement is provided in Norway, and most children typically bring packed lunches from home. The aim of this study was to investigate whether serving a free healthy school meal for one year resu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As provision of meals at school has become a political priority in Norway, studies on the introduction and evaluation of school meals in Norway are increasing [32,[34][35][36][37]62]. However, there is a lack of studies including a wide sample of pupils, teachers and parents.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As provision of meals at school has become a political priority in Norway, studies on the introduction and evaluation of school meals in Norway are increasing [32,[34][35][36][37]62]. However, there is a lack of studies including a wide sample of pupils, teachers and parents.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In Norway, there have been several initiatives and pilot projects to test different school meal models and how school meals could be implemented [30,31]. The few intervention studies that have been conducted have generally shown an association with a healthier diet [28,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%